A case scenario study on adherence to GINA recommendations by primary care physicians in an area of Southern Italy: the “Progetto Padre 2.0” - Mauro Maniscalco; Claudio Candia; Marta Coppola; Silvestro Ennio D’Anna; Carmen Lombardi; Claudia Merola; Antonio Iovine; Pasquale Ambrosino; Antonio Molino; Salvatore Fuschillo (BMC Primary Care)
Abstract Background Accurate diagnosis and management of bronchial asthma are complex processes guided by national and international asthma guidelines, particularly the Global Initiative for Asthma (GINA). However, adherence to these guidelines is often suboptimal, varying across healthcare professionals and countries, which can lead to poor asthma control and increased healthcare costs. Aim In this observational study, we assessed the alignment to GINA recommendations in the diagnosis and management of asthma among 15 primary care physicians in two metropolitan areas of the Campania region, Southern Italy. Methods 120 patients were randomly selected from the electronic medical records of 15 primary care physicians. Afterwards, the alignment of diagnostic pathways and treatments with current GINA recommendations was assessed by an experienced chest physician. Three main outcomes were defined: diagnostic congruence, diagnostic workup congruence, and therapeutic congruence. Results Overall, 26.7% of our sample presented with an incongruous asthma diagnosis, while only 46.7% patients had therapeutic prescriptions in line with the latest GINA document recommendations. Patients treated in accordance with GINA recommendations exhibited significantly higher ACT scores, averaging 20.5 ± 4.0, compared to those receiving non-guideline-directed therapy, who averaged 15.7 ± 6.1 (p < 0.001). Diagnostic congruence showed a direct correlation with atopy (r = 0.277, p = 0.002) and an inverse correlation with ACT score (r = -0.335, p < 0.001). Conclusions The results of this study indicate that adherence to asthma guidelines in the metropolitan areas of Naples and Benevento remains insufficient. Further research focused on developing individualized interventions to manage non-adherence is warranted.